Ekonomické zhodnocení Evropské měnové unie - Sponer, Miroslav (Univerzita Pardubice, 1999)
This paper analyzes the impact of a monetary union. The author identifies the main costs and benefits of a monetary union. Costs are the result of a loss of macroeconomic stability, benefits result from microeconomic efficiency gains. The discussion has been based on an economic cost-benefit analysis. Countries may also decide to adopt a common curency for political reasons.
Keywords: Evropská měnová unie; Ekonomika; Analýza